THE INFLUENCE OF EXTERNAL FACTORS, SCHOOL SCOPE ON STUDENT’S LEARNING OUTCOMES IN MATHEMATICS CLASS X THE DEPARTMENT OF SCIENCE AT SMAN 1 PANJI - Lisma Dian Kartika Sari; Ida Fitriana Ambarsari; Eric Dwi Putra; Nur Hasanah (Journal on Research and Review of Educational Innovation, 2023)
This study aims to determine the influence of external factor in the scope of the school student learning outcomes in mathematic subjects specialization in class X sciences in Panji 1 Senior High School. In this study examined 3 independent variables contained in external factors in the scope of the school, namely the learning methods used by teachers, learning media, and socializing. This study in determining respondents using the proportional random sampling method, which consists of 177 populations of class X science students and taken 100 students as samples. The research design used was ex-post facto design. Retrieval of independent variable data using a questionnaire and Likert scale. Bound Variable Data using the method of documentation. Data analysis uses multiple linear regression analysis. The results of data analysis obtained the value of the correlation coefficient (r-count) of 0,014 and F count of 0,443, while F table of 2,70 at N = 100 with a significance level 5% means F count < F table .